Phosphate positive electrode material and preparation method and application thereof

By controlling the particle size of the phosphate-based positive electrode material and adding anionic substances during the preparation process, the problem of excessively wide particle size distribution of the positive electrode material is solved, and the thermal stability and cyclic stability of the material are significantly improved.

CN119650627APending Publication Date: 2025-03-18SHENZHEN DYNANONIC CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411734211.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The particle size distribution of existing phosphate-based positive electrode materials is too wide, resulting in poor overall performance, especially in high-temperature storage performance, thermal stability and cycling performance.

Method used

By controlling the minimum particle size of the phosphate-based positive electrode material ≥80nm, and adding anionic substances and carbon sources during the preparation process to form a solid solution, promoting sintering treatment, reducing the large size of the particles, and ensuring narrow and uniform particle size distribution.

Benefits of technology

The uniformity of particle size distribution is achieved, the thermal stability, high-temperature storage performance and cycle stability of the material are improved, and the overall performance of lithium-ion batteries is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650627A_ABST
    Figure CN119650627A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion batteries, in particular to a phosphate positive electrode material and a preparation method and application thereof. Provided is a phosphate-based positive electrode material having a minimum particle diameter of 80 nm or more and a particle diameter dispersion coefficient (PDI) of less than 0.4. The minimum particle size of particles of the phosphate positive electrode material is controlled to be greater than or equal to 80nm, so that fine powder particles less than 80nm cannot appear in the particles, and the stability of a crystal structure of the material is improved, so that the overall thermal stability and cycle performance of the material are improved; the particle size dispersion coefficient PDI is further controlled to be less than 0.4, and when the particle size dispersion coefficient is smaller, the distribution of the positive electrode material is more uniform, so that the phosphate positive electrode material with narrow particle size distribution and uniform particle size is obtained, the processing performance of the material is effectively improved, and the rate cycle stability is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of lithium-ion batteries, and in particular relates to a phosphate-based positive electrode material and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries are an efficient, environmentally friendly, and renewable energy device. Due to their high energy density, light weight, and low self-discharge, they have become the main energy device in traditional 3C products, electric vehicles, energy storage, and other fields. Lithium-ion positive electrode materials are one of the important components of lithium-ion batteries, and their performance directly determines the performance and life of lithium-ion batteries.

[0003] Phosphate-based cathode materials have low intrinsic conductivity, so the particle size needs to be reduced to increase the lithium ion migration rate and ensure the electrical properties of the material. In the process of particle refinement, there will be a large number of fine powder particles smaller than 80nm. Particles that are too small will have high interface effects, many crystal defects, and unstable crystal structures, resulting in poor high-temperature storage performance, thermal stability, and cycle performance. Increasing the roasting temperature will increase the particle size of fine powder particles, while causing large particles to be too large and unable to fully utilize their capacity; it can be seen that the uneven distribution of particle size in the cathode material seriously affects the overall properties of the cathode material.

[0004] Therefore, there is an urgent need to provide a method for controlling the particles of the positive electrode material to eliminate the fine powder particles that are too small in the positive electrode material and control the maximum growth particle size of the grains, so as to effectively improve the problem of poor overall performance caused by the wide particle size distribution of the positive electrode material particles. Summary of the invention

[0005] The purpose of the present application is to provide a phosphate-based positive electrode material and a preparation method and application thereof, aiming to solve the problem in the prior art that the positive electrode material particle size distribution is too wide, resulting in poor overall performance.

[0006] In order to achieve the above application purpose, the technical solution adopted in this application is as follows:

[0007] In a first aspect, the present application provides a phosphate-based positive electrode material, wherein the minimum particle size of the phosphate-based positive electrode material is ≥80 nm, and the particle size dispersion coefficient PDI is <0.4.

[0008] In some embodiments, the particle size of the phosphate-based positive electrode material is 80 nm to 500 nm.

[0009] In some embodiments, the phosphate-based positive electrode material includes an active core material and a carbon layer coated on the outer surface of the active core material, wherein the active core material is selected from phosphates containing doping elements formed by anionic substances.

[0010] In some embodiments, the phosphate includes any one of lithium iron phosphate, lithium manganese phosphate, lithium vanadium phosphate, and lithium manganese iron phosphate.

[0011] In some embodiments, the anionic species is selected from any one of oxides, nitrides, and polyanionic compounds.

[0012] In some embodiments, the anionic material includes any one of ammonium sulfate, phosphoric acid, ammonium hydrogen phosphate, boric acid, silicic acid, silicon dioxide, and silicon nitride.

[0013] In some embodiments, the doping element includes any one of phosphorus, boron, silicon, and sulfur.

[0014] In a second aspect, the present application provides a method for preparing a phosphate-based positive electrode material, comprising the following steps:

[0015] Providing a phosphate precursor material, and subjecting the phosphate precursor material to a first sintering treatment to obtain a phosphate pre-product;

[0016] The anion substance, the carbon source and the phosphate-based pre-product are mixed and subjected to a second sintering treatment to obtain a phosphate-based positive electrode material.

[0017] In some embodiments, the minimum particle size of the phosphate-based positive electrode material is ≥80 nm.

[0018] In some embodiments, the carbon source includes any one of glucose, sucrose, PVDF, carbon black, PEG, paraffin, graphite, and graphene.

[0019] In some embodiments, the mass of the anionic substance is 0.1 wt % to 1 wt % of the mass of the phosphate-based pre-product.

[0020] In some embodiments, the mass of the carbon source is 1 wt % to 10 wt % of the mass of the phosphate-based pre-product.

[0021] In some embodiments, the first sintering process is performed at a temperature of 400° C. to 600° C. for 8 to 12 hours.

[0022] In some embodiments, the second sintering process is performed at a temperature of 650° C. to 800° C. for a time of 4 to 8 hours.

[0023] In some embodiments, in the step of mixing the anionic substance, the carbon source, and the phosphate-based pre-product, the anionic substance forms a solid solution with the phosphate-based pre-product.

[0024] In a third aspect, the present application provides a positive electrode plate, which includes a current collector and a positive electrode active layer formed on the surface of the current collector, and the positive electrode active layer includes the above-mentioned phosphate-based positive electrode material or the phosphate-based positive electrode material prepared by the above-mentioned method for preparing the phosphate-based positive electrode material.

[0025] In a fourth aspect, the present application provides a secondary battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the positive electrode sheet is selected from the above-mentioned positive electrode sheets.

[0026] The phosphate-based positive electrode material provided in the first aspect of the present application first controls the minimum particle size of the phosphate-based positive electrode material to be ≥80nm, ensuring that no fine powder particles smaller than 80nm appear in the particles, thereby improving the stability of the material's crystal structure and improving the overall thermal stability and cycle performance of the material; further controls the particle size dispersion coefficient PDI to be less than 0.4. The smaller the particle size dispersion coefficient, the more uniform the distribution of the positive electrode material. Therefore, a phosphate-based positive electrode material with a narrow particle size distribution and uniform particle size is obtained, which effectively improves the material processing performance and enhances the rate cycle stability.

[0027] The second aspect of the present application provides a method for preparing a phosphate-based positive electrode material, in which an anionic substance is added to a phosphate-based pre-product, and the anionic substance reacts with the fine particles of the phosphate-based pre-product to form a solid solution with the main crystalline phase, which not only changes the proportion of cations and anions in the positive electrode material, eliminates fine powder particles in the positive electrode material of a lithium-ion battery, but also promotes the second sintering treatment, reduces the temperature of the second sintering treatment, effectively reduces the large size of the particles, and greatly reduces the proportion of oversized particles, thereby ensuring that the prepared phosphate-based positive electrode material has uniform particle size, a narrow particle size distribution, and a small particle size dispersion coefficient, which is beneficial to the capacity of the material and improves the high temperature stability of the material. The preparation method is simple and easy to operate, does not require the use of large instruments and equipment, and is conducive to widespread use.

[0028] The positive electrode plate provided in the third aspect of the present application includes the above-mentioned phosphate-based positive electrode material or the phosphate-based positive electrode material prepared by the preparation method of the above-mentioned phosphate-based positive electrode material. Based on the above-mentioned phosphate-based positive electrode material being uniform in size and having excellent electrochemical properties, the obtained positive electrode plate has a high rate performance and can be widely used in various types of secondary batteries.

[0029] The secondary battery provided in the fourth aspect of the present application includes the above-mentioned positive electrode plate with high rate performance. Therefore, the obtained secondary battery has high cycle efficiency and high charge and discharge specific capacity. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0031] Figure 1 This is a scanning electron microscope analysis image of the phosphate-based positive electrode material provided in Example 1 of the present application.

[0032] Figure 2 This is a scanning electron microscope analysis diagram of the phosphate-based positive electrode material provided in Comparative Example 1 of the present application. DETAILED DESCRIPTION

[0033] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0034] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.

[0035] In this application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0036] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.

[0037] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "an" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0038] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass in the embodiment description of the present application can be μg, mg, g, kg and other mass units known in the chemical industry.

[0039] The terms "first" and "second" are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. For example, without departing from the scope of the embodiments of the present application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Thus, features defined as "first" and "second" may explicitly or implicitly include one or more of the features.

[0040] A first aspect of an embodiment of the present application provides a phosphate-based positive electrode material, wherein the minimum particle size of the phosphate-based positive electrode material is ≥80 nm, and the particle size dispersion coefficient PDI is <0.4.

[0041] The phosphate-based positive electrode material provided in the first aspect of the embodiment of the present application first controls the minimum particle size of the phosphate-based positive electrode material to be ≥80nm, ensuring that no fine powder particles smaller than 80nm appear in the particles, thereby improving the stability of the crystal structure of the material and improving the overall thermal stability and cycle performance of the material; further controls the particle size dispersion coefficient PDI to be less than 0.4. The smaller the particle size dispersion coefficient, the more uniform the distribution of the positive electrode material. Therefore, a phosphate-based positive electrode material with a narrow particle size distribution and uniform particle size is obtained, which effectively improves the material processing performance and enhances the rate cycle stability.

[0042] The dispersion coefficient PDI of the controlled particle size is less than 0.4. The dispersion coefficient PDI is used to measure the degree of data dispersion. The dispersion coefficient PDI of the controlled particle size is less than 0.4, which means that the fine powder particles of the positive electrode material account for a small proportion, and the size of the largest particles of the positive electrode material needs to be properly controlled to ensure that the particle size distribution of the positive electrode material is narrower, which is conducive to effectively improving the material processing performance and enhancing the rate cycle stability.

[0043] In some embodiments, the particle size of the phosphate-based positive electrode material is 80nm to 500nm. Ensure that the diameter of the smallest particle is greater than / equal to 80nm, control the proportion of fine powder particles in the positive electrode material particles to reduce fine powder particles; further control the size of the largest particle to 500nm; control the maximum theoretical growth size of the crystal particles to ensure the capacity of the material to improve the electrochemical performance of the material. In some specific embodiments, the particle size of the phosphate-based positive electrode material includes but is not limited to 80nm, 90nm, 100nm, 110nm, 120nm, 130nm, 140nm, 150nm, 160nm, 170nm, 180nm, 190nm, 200nm, 300nm, 400nm, 500nm,.

[0044] In some embodiments, the phosphate-based positive electrode material includes an active core material and a carbon layer coated on the outer surface of the active core material, wherein the active core material is selected from a phosphate containing a doping element formed by an anionic substance. In some embodiments, the phosphate includes any one of lithium iron phosphate, lithium manganese phosphate, lithium vanadium phosphate, and lithium manganese iron phosphate.

[0045] In some embodiments, the anionic material is selected from any one of oxides, nitrides and polyanionic compounds. In some embodiments, the anionic material includes any one of ammonium sulfate, phosphoric acid, ammonium hydrogen phosphate, boric acid, silicic acid, silicon dioxide and silicon nitride.

[0046] In some embodiments, the doping element includes any one of phosphorus, boron, silicon, and sulfur. The doping element formed can change the ratio of anions and cations in the material itself, making the particles more uniform, reducing the overall specific surface area of ​​the material, and improving processing performance.

[0047] A second aspect of the present application provides a method for preparing a phosphate-based positive electrode material, comprising the following steps:

[0048] S01. Providing a phosphate precursor material, and subjecting the phosphate precursor material to a first sintering treatment to obtain a phosphate pre-product;

[0049] S02. Mix the anion substance, the carbon source and the phosphate-based pre-product, and perform a second sintering treatment to obtain a phosphate-based positive electrode material.

[0050] The second aspect of the present application provides a method for preparing a phosphate-based positive electrode material. In the preparation method, an anionic substance is added to a phosphate-based pre-product, and the anionic substance reacts with the fine particles of the phosphate-based pre-product to form a solid solution with the main crystalline phase, which not only changes the proportion of cations and anions in the positive electrode material, eliminates fine powder particles in the positive electrode material of a lithium-ion battery, but also promotes the second sintering treatment, reduces the temperature of the second sintering treatment, effectively reduces the large size of the particles, and greatly reduces the proportion of oversized particles, thereby ensuring that the prepared phosphate-based positive electrode material has uniform particle size, a narrow particle size distribution, and a small particle size dispersion coefficient, which is beneficial to the capacity of the material and improves the high temperature stability of the material. The preparation method is simple and easy to operate, does not require the use of large instruments and equipment, and is conducive to widespread use.

[0051] In step S01, a phosphate-based precursor material is provided, and the phosphate-based precursor material is subjected to a first sintering treatment to obtain a phosphate-based pre-product.

[0052] In some embodiments, the phosphate-based precursor material can be prepared by different methods such as a solid phase method, a gel method or a liquid phase method.

[0053] In some specific embodiments, the phosphate-based precursor material is prepared by a liquid phase method, and the preparation method includes: taking a certain amount of Li source, Fe source, phosphorus source, manganese source, and additives, mixing them in a certain ratio, and preparing the phosphate-based precursor material by a liquid phase method.

[0054] In some embodiments, the Li source is at least one of Li2O, Li2CO3, LiH2PO4, LiOH·H2O, CH3COOLi, and LiNO3; the Fe source is at least one of FeCl3, Fe(NO3)3, Fe2O3, and FeSO4·7H2O; the phosphorus source is at least one of (NH4)3PO4, LiH2PO4, and H3PO4; and the manganese source is at least one of MnO2, Mn(NO3)2, MnSO4, and Mn3(PO4)2·3H2O.

[0055] Furthermore, the phosphate-based precursor material is subjected to a first sintering treatment to obtain a phosphate-based pre-product.

[0056] In some embodiments, the first sintering process is performed at a temperature of 400° C. to 600° C. for 8 to 12 hours.

[0057] In some specific embodiments, the temperature of the first sintering process includes but is not limited to 400° C., 420° C., 450° C., 480° C., 500° C., 520° C., 550° C., 580° C., and 600° C. The time of the first sintering process includes but is not limited to 8 hours, 8.5 hours, 9 hours, 9.5 hours, 10 hours, 10.5 hours, 11 hours, 11.5 hours, and 12 hours.

[0058] In some embodiments, the first sintering process is performed in a protective atmosphere, which includes any one of argon, nitrogen, argon-hydrogen mixed gas, argon-methane mixed gas, nitrogen-methane mixed gas, or nitrogen-hydrogen mixed gas, or a combination of at least two thereof.

[0059] In step S02, the anion substance, the carbon source and the phosphate-based pre-product are mixed and subjected to a second sintering treatment to obtain a phosphate-based positive electrode material.

[0060] Anionic substances refer to anions including oxides, nitrides or polyanions. Anionic substances are added to react with fine particles of positive electrode materials, and the anionic substances form a solid solution with the main crystal phase, which promotes sintering, reduces the sintering temperature, effectively reduces the proportion of oversized particles, changes the ratio of cations to anions in the positive electrode material, and changes the material structure, wherein particles with a high proportion of anions can form larger particles. In some embodiments, the anionic substance includes any one of ammonium sulfate, phosphoric acid, ammonium hydrogen phosphate, boric acid, silicic acid, silicon dioxide, and silicon nitride.

[0061] In some embodiments, the mass of the anionic substance is 0.1 wt% to 1 wt% of the mass of the phosphate pre-product. If the mass of the anionic substance added is too small, the particle size will not change significantly; if the amount added is too large, impurities will be easily formed, affecting the properties of the material.

[0062] In some specific embodiments, the mass of the anionic substance as the mass of the phosphate-based pre-product includes but is not limited to 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, and 1.0wt%.

[0063] Providing a carbon source is mainly to form a carbon coating layer. In some embodiments, the carbon source includes any one of glucose, sucrose, PVDF, carbon black, PEG, paraffin, graphite, and graphene.

[0064] In some embodiments, the mass of the carbon source is 1 wt% to 10 wt% of the mass of the phosphate pre-product. If the amount of carbon source added is too little, a dense carbon coating layer cannot be formed; if the amount of carbon source added is too much, the formed carbon coating layer is too thick, affecting the properties of the positive electrode material.

[0065] In some specific embodiments, the mass of the carbon source is the mass of the phosphate-based pre-product, including but not limited to 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, and 10wt%.

[0066] In some embodiments, the temperature of the second sintering treatment is 650°C to 800°C, and the time is 4 to 8 hours. Controlling the temperature of the second sintering treatment to be relatively low can effectively reduce energy, thereby effectively reducing the size of the particles, so as to control the maximum theoretical growth size of the crystal particles, ensure that the difference between the particle size of the largest particle and the smallest particle is small, and thereby ensure that the particle size dispersion coefficient PDI of the particles is less than 0.4, ensure that the particle size distribution is narrow, effectively improve the material processing performance, and enhance the rate cycle stability. If the temperature of the second sintering treatment is lower than 650°C, the material will have poor crystallinity and poor performance; if the temperature of the second sintering treatment is too high, the particle size will be too large, affecting the particle size dispersion coefficient, which is not conducive to improving the material rate cycle stability.

[0067] In some specific embodiments, the temperature of the second sintering process includes, but is not limited to, 650° C., 680° C., 700° C., 720° C., 750° C., 780° C., and 800° C. The time of the second sintering process includes, but is not limited to, 4 hours, 4.5 hours, 5 hours, 5.5 hours, 6 hours, 6.5 hours, 7 hours, 7.5 hours, and 8 hours.

[0068] In some embodiments, the second sintering process is performed in a protective atmosphere, which includes any one of argon, nitrogen, argon-hydrogen mixed gas, argon-methane mixed gas, nitrogen-methane mixed gas, or nitrogen-hydrogen mixed gas, or a combination of at least two thereof.

[0069] In some embodiments, in the step of mixing anionic substances, carbon sources and phosphate-based pre-products, the anionic substances and the phosphate-based pre-products form a solid solution; the purpose is to promote sintering, reduce the sintering temperature, effectively reduce the proportion of oversized particles, change the ratio of cations and anions in the positive electrode material, and change the material structure.

[0070] In some embodiments, the minimum particle size of the phosphate-based positive electrode material is ≥80 nm.

[0071] A third aspect of an embodiment of the present application provides a positive electrode plate, which includes a current collector and a positive electrode active layer formed on the surface of the current collector, and the positive electrode active layer includes the above-mentioned phosphate-based positive electrode material or a phosphate-based positive electrode material prepared by the above-mentioned method for preparing the phosphate-based positive electrode material.

[0072] The positive electrode plate provided in the third aspect of the embodiment of the present application includes the above-mentioned phosphate-based positive electrode material or the phosphate-based positive electrode material prepared by the preparation method of the above-mentioned phosphate-based positive electrode material. Based on the above-mentioned phosphate-based positive electrode material being uniform in size and having excellent electrochemical properties, the obtained positive electrode plate has a high rate performance and can be widely used in various types of secondary batteries.

[0073] A fourth aspect of an embodiment of the present application provides a secondary battery, the secondary battery comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the positive electrode sheet is selected from the above-mentioned positive electrode sheets.

[0074] The secondary battery provided in the fourth aspect of the present application includes the above-mentioned positive electrode plate with high rate performance. Therefore, the obtained secondary battery has high cycle efficiency and high charge and discharge specific capacity.

[0075] The following describes the invention in conjunction with specific embodiments.

[0076] Example 1

[0077] A phosphate-based positive electrode material and a preparation method thereof

[0078] The preparation method comprises the following steps: ① 19.30 g Li2CO3, 36.98 g Fe2O3, 200 g (NH4)3PO4, 0.08 g MnO2 and additives are mixed evenly, and LiMn is prepared by self-thermal evaporation liquid phase method. 0.03 Fe 0.97 PO4 precursor;

[0079] ②LiMn 0.03 Fe 0.97 The PO4 precursor was heated to 500°C at a rate of 6°C / min under nitrogen atmosphere and kept at this temperature for 9h;

[0080] ③ Take out the sample, add 4% sucrose and 1% phosphoric acid of the sample mass, mix and crush, and calcine at 800℃ for 5h under nitrogen atmosphere. After crushing, the sample can obtain the phosphate positive electrode material LiMn 0.03 Fe 0.97 PO4@P 0.1 (SEM image of the phosphate-based positive electrode material obtained in Example 1 is as follows Figure 1 shown).

[0081] Example 2

[0082] A phosphate-based positive electrode material and a preparation method thereof

[0083] Compared with the preparation method provided in Example 1, the "1% phosphoric acid" in step ③ is modified to "0.5% phosphoric acid", and the other steps are the same to obtain the phosphate-based positive electrode material LiMn 0.03 Fe 0.97 PO4@P 0.05 .

[0084] Example 3

[0085] A phosphate-based positive electrode material and a preparation method thereof

[0086] Compared with the preparation method provided in Example 1, the "1% phosphoric acid" in step ③ is changed to "0.5% boric acid", and the other steps are the same to obtain the phosphate-based positive electrode material LiMn 0.03 Fe 0.97 PO4@B 0.05 .

[0087] Comparative Example 1

[0088] A phosphate-based positive electrode material and a preparation method thereof

[0089] Compared with the preparation method provided in Example 1, the "1% phosphoric acid" in step ③ is deleted, and the other steps are the same to obtain the phosphate-based positive electrode material LiMn 0.03 Fe 0.97 PO4.

[0090] Comparative Example 2

[0091] A phosphate-based positive electrode material and a preparation method thereof

[0092] Compared with the preparation method provided in Example 1, the "1% phosphoric acid" in step ③ is changed to "5% boric acid", and the other steps are the same to obtain the phosphate-based positive electrode material LiMn 0.03 Fe 0.97 PO4@B 0.5 .

[0093] Comparative Example 3

[0094] A phosphate-based positive electrode material and a preparation method thereof

[0095] Compared with the preparation method provided in Example 1, the step ③ of "calcining at 800°C for 5h" is changed to "calcining at 900°C for 5h", and the other steps are the same to obtain the phosphate-based positive electrode material LiMn 0.03 Fe 0.97 PO4@P 0.1 -1.

[0096] Preparation of lithium-ion batteries:

[0097] 800g of the positive electrode active components of Examples 1 to 3 or Comparative Examples 1 to 3, 100g of the conductive agent acetylene black, and 100g of the binder polyvinylidene fluoride (PVDF) were added to 800g of N-methylpyrrolidone solution (NMP solution), and stirred in a vacuum mixer for 2h to prepare a positive electrode slurry; the slurry was evenly coated on an aluminum foil, and then placed in a vacuum drying oven at 120°C for 12h, and then rolled and punched into a 14mm diameter disc as a positive electrode sheet. The positive electrode sheet, the negative electrode sheet (a metal lithium sheet with a diameter of 14.5mm), the separator (Celgard 2400 microporous polypropylene membrane) and the electrolyte (1mol / L LiPF6 / EC+DMC (volume ratio 1:1)) were assembled into a CR2025 button lithium ion battery in a glove box filled with an inert atmosphere.

[0098] Performance Testing

[0099] ① Determination of particle size dispersion coefficient: Determination of particle size dispersion coefficient of phosphate-based positive electrode materials of Examples 1 to 3 and Comparative Examples 1 to 3.

[0100] ②Electrochemical performance test: The test batteries in the prepared embodiments and comparative examples were subjected to charge and discharge tests using a lithium-ion battery charge and discharge test system at 25±0.5℃ / 60±0.5℃. The charge and discharge conditions were: charge end voltage 4.3V; discharge end voltage 2V; charge and discharge current density: 0.1C, charge and discharge; 1C, cycle 2000 / 1000 weeks. Test capacity and capacity retention rate.

[0101] Results Analysis

[0102] The performance test results are shown in Table 1. The particle size of the positive electrode materials obtained in Examples 1 to 3 and Comparative Examples 1 to 3 is subjected to the dispersion coefficient. It can be seen that the dispersion coefficients PDI of the positive electrode materials obtained in Examples 1 to 3 are 0.32, 0.39, and 0.38, respectively, and PDI < 0.4. It can be seen that the particle size distribution of the obtained positive electrode materials is narrow. The dispersion coefficients PDI of the positive electrode materials obtained in Comparative Examples 1 to 3 are 0.5, 0.29, and 0.41, respectively. Among them, in Comparative Example 2, anionic substances are added, and the second sintering temperature is kept at a relatively low temperature, and the particle size distribution of the obtained positive electrode material particles is narrow. Comparative Example 1 does not add anionic substances, and the dispersion coefficient PDI of the obtained positive electrode material particles is greater than 0.4, and the particle size distribution is wide; although anionic substances are added in Comparative Example 3, the calcination temperature is too high, resulting in more particles with larger particle sizes, so the particle dispersion coefficient PDI is greater than 0.4.

[0103] Furthermore, the electrochemical performance of the battery assembled from each material was tested, and the test results are shown in Table 1. The battery assembled from the materials obtained in Examples 1 to 3 has an initial discharge capacity of more than 157.4 mAh / g at 25°C and 0.1C, and a capacity retention rate of more than 90.5% after 1000 cycles at 60°C and 1C; and a capacity retention rate of more than 78.1% after 2000 cycles at 25°C and 1C.

[0104] In the positive electrode material preparation method provided in Comparative Example 1, no anionic substances are added, so the obtained positive electrode material particle dispersion coefficient PDI>0.4, the particle size distribution is wide, and the assembled battery has a high first discharge capacity value of 157.5mAh / g under 0.1C conditions; however, after 1000 cycles at 60°C and 1C conditions, the capacity retention rate is only 43.1%; after 2000 cycles at 25°C and 1C conditions, the capacity retention rate is only 68.4%. It can be seen that the battery obtained in Comparative Example 1 has a low capacity retention rate and poor cycle stability due to the excessively large particle size dispersion coefficient of the positive electrode material and the excessively wide particle size distribution of the particles.

[0105] In the positive electrode material preparation method provided in Comparative Example 2, "5% anionic substance" is added. Although the obtained positive electrode material particle dispersion coefficient PDI is less than 0.4, and the initial discharge capacity is as high as 150.3 mAh / g under 0.1C conditions; however, after 1000 cycles at 60°C and 1C conditions, the capacity retention rate is only 59.4%; after 2000 cycles at 25°C and 1C conditions, the capacity retention rate is only 70.0%. It can be seen that compared with Examples 1 to 3, the amount of anionic substance added in Comparative Example 2 is too much, which introduces impurities into the positive electrode material, thereby affecting the capacity retention rate and cycle stability of the positive electrode material.

[0106] In the positive electrode material preparation method provided in Comparative Example 3, an appropriate amount of anionic substances is added, but the temperature of the second sintering treatment is too high, and the maximum particle size of the obtained particles is too large, resulting in a dispersion coefficient PDI>0.4, and under 0.1C conditions, the first discharge capacity value is relatively low, only 148.7mAh / g; after 1000 cycles at 60°C and 1C conditions, the capacity retention rate is only 63.3%; after 2000 cycles at 25°C and 1C conditions, the capacity retention rate is only 70.3%. It can be seen that although an appropriate amount of anionic substances is added in Comparative Example 3, the temperature of the second sintering treatment is too high, which affects the overall rate cycle performance of the material.

[0107] Table 1

[0108]

[0109] The SEM image of the phosphate-based cathode material obtained in Example 1 is as follows: Figure 1 As shown, the SEM image of the phosphate-based positive electrode material obtained in Comparative Example 1 is as follows Figure 2 As shown, and combined with Table 1, it can be seen that the minimum particle size of the phosphate-based positive electrode material obtained in Example 1 is 123nm, and the minimum particle size of the phosphate-based positive electrode material obtained in Comparative Example 1 is 22nm. In summary, it can be analyzed that the phosphate-based positive electrode material particles obtained in Example 1 of the present application have a narrow particle size distribution and uniform particle size.

[0110] In summary, the phosphate-based positive electrode material provided in the present application eliminates fine powder particles smaller than 80 nm without reducing the capacity of the positive electrode material, and controls the particle size dispersion coefficient PDI to be less than 0.4. The smaller the particle size dispersion coefficient, the more uniform the distribution of the positive electrode material. Therefore, a phosphate-based positive electrode material with a narrow particle size distribution and uniform particle size is obtained, which significantly improves the thermal stability, high-temperature storage performance and cycle stability of the positive electrode material, and is conducive to wide application.

[0111] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.

Claims

1. A phosphate-based positive electrode material, characterized in that: The minimum particle size of the phosphate-based positive electrode material is ≥80 nm, and the particle size dispersion coefficient PDI is <0.

4.

2. The phosphate-based positive electrode material according to claim 1, characterized in that: The particle size of the phosphate-based positive electrode material is 80nm to 500nm.

3. The phosphate-based positive electrode material according to claim 1, characterized in that: The phosphate-based positive electrode material comprises an active core material and a carbon layer coated on the outer surface of the active core material, wherein the active core material is selected from phosphates containing doping elements formed by anionic substances.

4. The phosphate-based positive electrode material according to claim 3, characterized in that: The phosphate includes any one of lithium iron phosphate, lithium manganese phosphate, lithium vanadium phosphate, and lithium manganese iron phosphate; and / or, The anionic substance is selected from any one of oxides, nitrides and polyanionic compounds.

5. The phosphate-based positive electrode material according to claim 4, characterized in that: The anion substance includes any one of ammonium sulfate, phosphoric acid, ammonium hydrogen phosphate, boric acid, silicic acid, silicon dioxide, and silicon nitride; and / or, The doping element includes any one of phosphorus, boron, silicon and sulfur.

6. A method for preparing a phosphate-based positive electrode material, characterized in that: The steps include: Providing a phosphate precursor material, and subjecting the phosphate precursor material to a first sintering treatment to obtain a phosphate pre-product; The anion substance, the carbon source and the phosphate-based pre-product are mixed and subjected to a second sintering treatment to obtain a phosphate-based positive electrode material.

7. The method for preparing a phosphate-based positive electrode material according to claim 6, characterized in that: The minimum particle size of the phosphate-based positive electrode material is ≥80 nm; and / or, The carbon source includes any one of glucose, sucrose, PVDF, carbon black, PEG, paraffin, graphite, and graphene; and / or, The mass of the anionic substance is 0.1wt% to 1wt% of the mass of the phosphate pre-product; and / or, The mass of the carbon source is 1 wt% to 10 wt% of the mass of the phosphate-based pre-product.

8. The method for preparing a phosphate-based positive electrode material according to claim 6, characterized in that: The temperature of the first sintering treatment is 400° C. to 600° C., and the time is 8 to 12 hours; and / or, The temperature of the second sintering treatment is 650° C. to 800° C. and the time is 4 to 8 hours; and / or, In the step of mixing an anionic substance, a carbon source and the phosphate-based pre-product, the anionic substance forms a solid solution with the phosphate-based pre-product to promote sintering.

9. A positive electrode sheet, characterized in that: The positive electrode sheet includes a current collector and a positive electrode active layer formed on the surface of the current collector, and the positive electrode active layer includes the phosphate-based positive electrode material described in any one of claims 1 to 4 or the phosphate-based positive electrode material prepared by the method for preparing the phosphate-based positive electrode material described in any one of claims 5 to 8.

10. A secondary battery, characterized in that: The secondary battery comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the positive electrode sheet is selected from the positive electrode sheet according to claim 9.